Nanotechnology Issues Included in the Subjects of the Department of Biology in the Colleges of Education - Mazin Thamer Shanef 1, Mustafa Abdel Amir Raheem Al-Zamili1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This research aimed to: Recognize how much including in content of subjects in the Department of Biology College of Education in accordance with the Nanotechnology Issues. To achieve this aim, the researchers built a standard for the Nanotechnology Issues, were verified validity by presentation to a group of arbitrators specialists in the methods of teaching the Biology , and that standard is finalized be from (8) Nanotechnology Issues and emerged of them (90) sub- Issues, then the researchers analyzed the content of subjects of the Department of Biology in Colleges of Education for the academic year (2018-2019) in the light of this criterion as the number of analyst was (12201) page, and it adopted the explicit idea and implicit idea as units for registration and repetition unit of the census, The results were : weakness of subjects in the Department of Biology in Colleges of Education to contain Nanotechnology Issues compared with the ratio based on the opinions of experts (20%), (16) only of 90 terms were achieved , that was equal of (17.77%)